1997
DOI: 10.1021/ja964230i
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bengal Rose Encapsulated in the Meijer Dendrimer Box

Abstract: We used molecular dynamics (MD) techniques to examine the encapsulation of Bengal Rose (BR) molecules in the Meijer dendrimer box (DBox) formed by the addition of tert-butyloxycarbonyl-l-Phe (tBOC-l-Phe) cap molecules to the 64 terminal primary amines of a fifth generation poly(propyleneimine) (PPI-5) dendrimer. Using a large periodic box (including DBox, four to six BR, and CH2Cl2 solvent, totaling ∼25 000 atoms), we examined the MD of these systems for ∼0.5 ns. Without the cap we find that BR molecules estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 17 publications
1
57
0
1
Order By: Relevance
“…[22] Molecules of different sizes, such as 7,7,8,8-tetracyano-para-quinodimethane (TCNQ) or the dye rose bengal were trapped during dendrimer synthesis; UV/Vis spectroscopy showed that rose bengal was encapsulated with an average of one molecule per dendritic box. [23,24] Figure 4. A dendritic box capable of trapping and encapsulating guest molecules during construction.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Molecules of different sizes, such as 7,7,8,8-tetracyano-para-quinodimethane (TCNQ) or the dye rose bengal were trapped during dendrimer synthesis; UV/Vis spectroscopy showed that rose bengal was encapsulated with an average of one molecule per dendritic box. [23,24] Figure 4. A dendritic box capable of trapping and encapsulating guest molecules during construction.…”
Section: Discussionmentioning
confidence: 99%
“…DOX was loaded using an equilibrium dialysis method as described previously [26,27]. 1 mg of DOX hydrochloride was dissolved in 1 mL deionized water and mixed with 10 mg of PAMAM-PEG-WGA-Tf.…”
Section: Doxorubicin Loadingmentioning
confidence: 99%
“…Modeling was performed in a manner analogous to previous reports in the literature. [14][15][16][17] Molecular models were created using the Cerius 2 (version 4.0) software package (Molecular Simulations, Inc.; San Diego, CA). The DREIDING 18 force field version 2.21 was used for optimization and molecular dynamics simulations.…”
Section: Methodsmentioning
confidence: 99%